Semiparametric detection of changes in long range dependence - Fabrizio Iacone; Stepana Lazarova (Queen Mary University of London, School of Economics and Finance, 2017)
We consider changes in the degree of persistence of a process when the degree of persistence is characterized as the order of integration of a strongly dependent process. To avoid the risk of incorrectly specifing the data generating process we employ local Whittle estimates which uses only frequencies local at zero. The limit distribution of the test statistic under the null is not standard but it is well known in the literature. A Monte Carlo study shows that this inference procedure performs well in finite samples.
Keywords: C22; 330; Long memory; persistence; break; local Whittle estimate